Asset Pricing Models in Indian Capital Markets - Dash, Mihir; N., Rishika (Indian Journal of Finance, 2011)
Asset pricing theory is a framework designed to identify and measure risk, as well as to assign rewards for bearing risk. There is a general contention that the simple Capital Asset Pricing Model (CAPM) does not adequately describe stock return behavior; other macro-economic factors may also play an important role. In particular, emerging capital markets like India provide a challenge to asset pricing theory; markets that have undertaken substantial liberalization of their financial sectors to allow for the free flow of foreign portfolio investments tend to be more sensitive to the macro-economic factors. The present study was based on a sample of fifty stocks listed in the S&P 500 index of the National Stock Exchange, belonging to eight of the most flourishing industries in the Indian economy. The objectives of the study were to compare and assess the CAPM and the Arbitrage Pricing Model (APM), as applied to Indian capital markets, and to find out how macroeconomic variables affect the returns of different securities.